Utilization of Zinner's Creativity in Developing the Rhythmic Pattern of the Blue Bedug Percussion Group as an Educational Medium in Early Childhood Education - MAYASARI, Mayasari; MULYANTI, Dety (Integration: Journal Of Social Sciences And Culture, 2025)
Purpose:The research entitled "Utilization of Zinner's Creativity in the Development of Rhythmic Patterns of the Blue Bedug Percussion Group as an Educational Media in Early Childhood Education" discusses how the results of Zinner's creative process in developing rhythmic patterns can have an impact on sensory and motor development in early childhood.Methodology:Rhodes' theory of the dimensions of creativity will discuss the process of creativity that can become educational media. Data collection techniques are carried out through observation, literature studies, interviews, and documentation.Findings:The results of this study show that Zinner's creativity in developing the rhythmic pattern of the blue bedug percussion group can be used as an educational medium in early childhood education.Implication:This study highlights that creativity in music is the result of a tortuous process involving internal and external drives, as well as a gradual accumulation of learning, interaction, and exploration. The composition Bedug Biru created by Zinner is clear proof of this, born from responsibility, cross-cultural knowledge, and experience to produce a work that suits the needs, audience, and abilities of the players.